Comparison of various membrane contactor systems for whey concentration process - Hasanoglu, Ayca (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2020)
Whey is a liquid by-product in dairy industry which can be used for a variety of purposes after treatment. It is rich in valuable components like proteins, lactose and minerals and thus the valorization of this by-product is essential. Whey should be concentrated until some certain concentrations by removing its water content. In this study the concentration of whey was carried out using membrane contactors. Whey was concentrated using hydrophobic hollow fiber polypropylene membrane contactors by means of osmotic driven osmotic distillation and temperature and pressure driven membrane distillation processes. In osmotic distillation the effects of several operating parameters on the water flux were investigated. After, the concentration process was carried out in two different membrane distillation processes of vacuum and direct contact membrane distillation and the effect of the temperature on flux was investigated. It was seen that the process was faster and more efficient in osmotic distillation compared to membrane distillation. However, in osmotic distillation the draw solution is diluted in time leading to a decrease in the activity difference which is the driving force of the process. In order to prevent this, osmotic distillation was coupled with membrane distillation and used as a hybrid. In the hybrid system, the process was carried out efficiently and higher fluxes were obtained due to working at higher activity differences. Furthermore, the diluted draw solution was recovered with the hybrid system.
Keywords: Whey; osmotic distillation; membrane distillation; membrane contactor; OSMOTIC CONCENTRATION; JUICE CONCENTRATION; PROCESS PARAMETERS; DISTILLATION; OSMOSIS; RECOVERY; PROTEINS; MILK; FLUX; Engineering